Singularity resolution in gauged supergravity and conifold unification - Edelstein Glaubach, José Daniel (2003)
We obtain a unified picture for the conifold singularity resolution. We propose that the gauged supergravity, through a novel prescription for the twisting, provides as appropriate framework to smooth out singularities in the context of gravity duals of supersymmetric gauge theories.